Collective ritual and social support networks in rural South India. Issue 1879 (30th May 2018) - Power, Eleanor A.
Abstract : The scholarship on religion has long argued that collective worship helps foster social cohesion. Despite the pervasiveness of this contention, rigorous quantitative evaluations of it have been surprisingly limited. Here, I draw on network data representing the ties of social support among Hindu residents of a South Indian village to evaluate the association between collective religious ritual and social cohesion. I find that those who partake in collective religious rituals together have a higher probability of having a supportive relationship than those who do not. At the structural level, this corresponds to denser connections among co-participants. At the individual level, participants are more embedded in the local community of co-religionists, but are not disassociating themselves from members of other religious denominations. These patterns hold most strongly for co-participation in the recurrent, low-arousal monthly worships at the temple, and are suggestive for co-participation in the intense and dysphoric ritual acts carried out as part of an annual festival. Together, these findings provide clear empirical evidence of the lasting relationship between collective religious ritual and social cohesion.